The effect of a therapeutic bath in malachite green on some haematological parameters of rainbow trout (Oncorhynchus mykiss, Walbaum, 1792) - Saglam, N; Ispir, U; Yonar, ME (Parlar Scientific Publications (P S P), 2003)
This study investigated the effect of a therapeutic bath in 1/15000 (66.67 mg/L) and 1/200000 (5 mg/L) concentrations of malachite green on the values of selected haemotological indicators of rainbow trout, On-corhyn-chus mykiss. During five days the fish were exposed to the above concentrations of malachite green for 30 seconds and 15 minutes, respectively. After the 5-days bath, in all the treated fish a significant decrease in leukocyte (p<0.001) and leucopaenia numbers, but no important decrease in that of erythrocytes (p>0.05), compared with control group findings, could be observed. In fish treated with 1/15000 malachite green, also a significant increase in haemoglobin, haemotocrit, and mean corpuscular volume (MCV) levels (p<0.01 and p<0.001) and in trouts exposed to 1/200000 malachite green a significant decrease in haemotocrit and MCV (p<0.001) and no significant decrease in haemoglobin (p>0.05) was found in comparison with control group findings. In fish exposed to both concentrations of malachite green also a significant increase of mean corpuscular haemoglobin (MCH) and mean corpuscular haemoglobin concentration (MCHC) levels (p<0.01 and p<0.001) could be observed.
Keywords: malachite green; Oncorhynchus mykiss; haematological parameters